2021
DOI: 10.3390/d13110590
|View full text |Cite
|
Sign up to set email alerts
|

Two New Species of the Genus Longipedia Claus, 1863 (Copepoda: Harpacticoida: Longipediidae) from Korea, with an Update and a Key to Species

Abstract: Benthic harpacticoids were collected from Korean waters. Two species were identified as members of the genus Longipedia Claus, 1863, because they have an extremely elongated distal segment of the P2 endopod. Longipedia koreana sp. nov. is morphologically most closely related to L. nichollsi Wells, 1980 and L. scotti Sars, 1903, but it can clearly be distinguished from both species based on the following morphological characteristics: P1 coxa with strong spinules near the outer margin and the distal element bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The opinion of Bang et al [1] to relegate Longipedia gonzalezi to a junior subjective of L. americana is not supported by the available data. We neither know if the Longipedia specimens that Onbé [3] collected were L. americana nor do we have access to these specimens for examination.…”
mentioning
confidence: 63%
See 4 more Smart Citations
“…The opinion of Bang et al [1] to relegate Longipedia gonzalezi to a junior subjective of L. americana is not supported by the available data. We neither know if the Longipedia specimens that Onbé [3] collected were L. americana nor do we have access to these specimens for examination.…”
mentioning
confidence: 63%
“…In the recent description of two new Longipedia species from Korea [1], the authors suggested that Longipedia gonzalezi Schizas et al, 2015 [2], described from Puerto Rico, northeast Caribbean Sea, should be relegated to a junior subjective synonym of L. americana Wells, 1980. This view is based on Onbé's work [3], where the naupliar and copepodid stages of L. americana are described [1].…”
mentioning
confidence: 99%
See 3 more Smart Citations